Prevalence of HIV and syphilis and their co-infection among men having sex with men in Asia: A systematic review and meta-analysis. Issue 3 (March 2023) - Mahmud, Sultan; Mohsin, Md; Muyeed, Abdul; Islam, Md Mynul; Hossain, Sorif; Islam, Ariful
Abstract: Background: Studies found that the group of men who have sex with men (MSM) is at a very high level of risk of HIV and sexually transmitted infections (STIs) in Asian regions due to multiple reasons. Although the prevalence of HIV among general people in Asia is considered low, the prevalence of HIV and Syphilis among MSM in this region was found very high and usually, it goes unnoticed. This study aimed to inspect the prevalence of and trends in HIV, Syphilis, and their co-infection among MSM in Asia. Methods: A systematic search was performed on January 5, 2021, in PubMed, Web of Science, and Google Scholar databases. To evaluate the heterogeneity, Q-tests, and I 2 were used. To explore the publication bias, Eggers' test and funnel plot were used. The random-effect model and subgroup analysis were performed due to the significant heterogeneity. Results: A total of 2872 articles were identified, and 66 articles were included in the final analysis. The overall prevalence of HIV and Syphilis among MSM was estimated considering 69 estimates from 66 studies whereas 19 estimates of co-infection were found in 17 studies. The pooled HIV prevalence was 8.48% (CI: 7.01–9.95) and the pooled Syphilis prevalence was 9.86% (CI: 8.30–11.41) with significant heterogeneity and publication bias. The pooled prevalence of HIV and Syphilis co-infection was 2.99% (CI: 1.70–4.27) with significant heterogeneity and no publication bias. The HIV, Syphilis, and HIV-Syphilis co-infection prevalence estimates exhibited an upward trend during 2002–2017. Conclusions: HIV, Syphilis, and their co-infection are quite prevalent among MSM in the Asia-Pacific region. Integrated and intensified intervention strategies, HIV testing, and improved access to antiretroviral treatment as well as increased awareness are needed to reduce HIV, Syphilis, and their co-infection among the discussed vulnerable group.